Ursolic acid attenuates obesity-related metabolic dysfunction via modulation of peroxisome proliferator activated receptor-gamma in male Wistar rats fed with high-carbohydrate high-fat diet - Oluwatosin O. Omodara; Mohammed U. Kawu; Ibrahim G. Bako; Daniel H. Mhya; Theophilus T. Dawus (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background The risk factors of metabolic syndrome (MS) precedes the development of cardiovascular disease and type 2 diabetes and are largely triggered by high-carbohydrate high-fat diet (HCHFD) and sedentary lifestyle. The development of these risk factors is connected to persistent low-grade inflammation. Though, ursolic acid (UA) has been shown to prevent HCHFD-induced metabolic parameters. The present study aimed to elucidate the molecular mechanisms underlying the preventive effects of dietary UA supplementation on obesity-related metabolic disorders and inflammation in male Wistar rats fed with HCHFD. The animals were randomly divided into 4 groups (n = 5): 1—normal diet (ND) + distilled water (DW); 2—ND + UA; 3—HCHFD + DW; 4—HCHFD + UA. HCHFD was augmented with 20% fructose in drinking water. The animals were fed their respective diets daily for 20 weeks. 250 mg/kg body weight of ursolic acid was administered orally to UA-treated groups for the last 8 weeks. Blood samples were collected and liver and adipose tissues were harvested for biochemical and tissue analysis, respectively. Results BMI and FBG were significantly lowered in the HCHFD + UA-fed animals compared to the HCHFD + DW-fed animals. In the HCHFD + UA-fed animals, HOMA-IR, serum insulin, cholesterol, triglyceride and low-density lipoprotein cholesterol (LDL-C) were significantly decreased while high-density lipoprotein cholesterol (HDL-C) was increased compared to the HCHFD + DW-fed animals. UA significantly decreased serum tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) and increased adiponectin level compared to the HCHFD + DW-fed animals. The messenger ribonucleic acid (mRNA) level of peroxisome proliferator activated receptor-gamma (PPAR-γ) in adipose tissue was significantly upregulated while liver PPAR-γ mRNA level was significantly downregulated in HCHFD + UA-fed animals compared to HCHFD + DW group, respectively. UA restored the architecture of liver parenchyma to near normal. Conclusion Dietary UA supplementation mitigated metabolic dysfunction and inflammation associated with obesity via modulation of liver and adipose tissue PPAR-γ in male Wistar rats fed with HCHFD for 20 weeks.